PENINGKATAN KEMAMPUAN KELUARGA DALAM MERAWAT PASIEN GANGGUAN JIWA DI RUMAH MELALUI FAMILY GROUP EMPOWERMENT - Muliyadi, Muliyadi; DL Damanik, Hanna (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The national prevalence of households with mental disorders was 7/1000 of the population, and severe mental disorders was 9.8%. Mentally ill patients are often stigmatized by families and communities. Community service activities aimed at reduce family stigma in mentally ill patients, improve the knowledge and ability of families to care for mental disorder. Community service activities are carried out through the stages of home visits, family group discussions in puskesmas with group sharing about mental disorders and the role of families in care, family visits for mentoring and evaluation of activities. The target of the activities of ten mental and family disorder patients in the working area of Puskesmas Merdeka was carried out for three weeks. The results of community service showed a decrease in the stigma of mental disorder patients, increased knowledge and ability of family in early detection of mental health problems and self-assessment. Increasing the role of families through group sharing is an effective effort in the treatment of mental disorders at home.